Multi-Criteria Analysis for the Prioritization of Areas for the In Situ Conservation of Crataegus L., an Underutilized Fruit Tree in Mexico - Karina Sandibel Vera-Sánchez; Mauricio Parra-Quijano; Raúl Nieto-Ángel; Alejandro F. Barrientos-Priego (Plants, 2021)
Complementary ex situ and in situ conservation, including the on-farm alternative, is a highly desired and dynamic strategy that allows the natural evolution of the conserved germplasm. Due to the high costs involved, in addition to the limitations of both economic and human resources, in situ conservation must focus on areas where the greatest benefits are obtained, and the efforts made result in better impacts. Therefore, using spatial multi-criteria analysis and expert knowledge, 22 and 23 criteria were obtained as important for the conservation of wild and cultivated hawthorn, respectively. Criteria weights were calculated by the analytic hierarchy process and expert knowledge. The results showed species richness, phenotypic and ecogeographic diversity, and areas not covered by the official protected areas network were the most important criteria for in situ conservation of wild hawthorn. Prioritized areas were particularly focused in Chiapas, State of Mexico and Morelos. The prioritized areas for the in situ conservation of cultivated hawthorn were mostly defined by criteria such as number of cultivated varieties, number of uses, phenotypic diversity, ecogeographical diversity, and areas with rainfed agriculture. These areas were located mainly in Puebla. From this study, we propose a list of priority areas for the in situ conservation of both cultivated and wild hawthorn.